2006
DOI: 10.1007/s00464-006-9075-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an optimal gastric closure method for transgastric surgery

Abstract: The prototype device decreases procedure time and yields leak-resistant gastrotomy closures that are superior to clips and rival hand-sewn interrupted stitches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[ 1c , 6 ] However, tissue adhesives currently available in clinical practice present significant inherent limitations such as toxicity, insufficient strength, and/or excessive swelling. [ 1c , 6c , 7 ] Biomimetic approaches and new chemistries that yield polymer materials with adaptable adhesion strength are under development. [ 6b , e , 8 ] In practice, gluing or sealing with polymers remains a complex process: it requires both stringent storage and preparation conditions before in vivo glue application or in vivo initiation and control of chemical polymerization or cross-linking reactions.…”
mentioning
confidence: 99%
“…[ 1c , 6 ] However, tissue adhesives currently available in clinical practice present significant inherent limitations such as toxicity, insufficient strength, and/or excessive swelling. [ 1c , 6c , 7 ] Biomimetic approaches and new chemistries that yield polymer materials with adaptable adhesion strength are under development. [ 6b , e , 8 ] In practice, gluing or sealing with polymers remains a complex process: it requires both stringent storage and preparation conditions before in vivo glue application or in vivo initiation and control of chemical polymerization or cross-linking reactions.…”
mentioning
confidence: 99%
“…This is in contrast to the findings of Ryou et al who reported significantly low mean leak pressure of 33 mmHg. 12 In our study, a higher endoclip burst pressure could have resulted from closer placement of clips as on average we used 10 clips compared to Ryou's study using only 4-5 clips for closure. Our failed endoclip had given way at 15 mmHg; this was the result of a superficial bite of one edge by a central clip that was realized later at postmortem.…”
Section: Discussionmentioning
confidence: 73%
“…Although several methods of gastrotomy closure have been described in NOTES procedures to date, 1,[14][15][16][17][18][19] there has generally been a high incidence of postprocedure leakage from the incision site and limited follow-up. In our personal experience of more than 250 laboratory NOTES procedures, the gastric closure method that showed the greatest potential is the cardiac occluder being safe, rapid, and simple.…”
Section: Discussionmentioning
confidence: 99%